PROSEDUR PENGADAAN DAN PENGAMBILAN BARANG DI STORE HOTEL GRAN PURI MANADO - Agus Walansendow; Gloria Anastasia Saada; Bet El Silisna Lagarense1 (Jurnal Hospitaliti, 2024)
Procurement and retrieval procedures at the Gran Puri Manado hotel are often not in accordance with Operational Standards. Inappropriate procurement procedures result in goods often having vacancies in stock at the store, and picking up goods in stores that do not use a requisition form. The purpose of this study is to determine the importance of procuring goods at the store and to describe the procedures for procurement and expenditure of goods at the Gran Puri Manado hotel store. The analytical method used in this research is descriptive qualitative method, by explaining the importance of procurement of goods and procedures for procurement and retrieval of goods in accordance with the Standard Operational Procedure. The results of the study prove that making a Purchase request (PR) on time, taking into account the stock of goods will help operations so that it is not hampered and the stock in the store is still available, and there are no complaints from other departments for retrieval of goods. So that operations at the Gran Puri Manado hotel run well and there will be no complaints from any party. The storekeeper and purchasing must cooperate well with each other in paying attention to the stock of goods in the store and taking goods must also use a requisition form, as proof that the department that needs the goods has taken the goods.